Effects of plastic ingestion on blood chemistry, gene expression and body condition in wedge-tailed shearwaters (Ardenna pacifica) - Nicole Mejia; Flavia Termignoni-Garcia; Jennifer Learned; Jay Penniman; Scott V. Edwards (PeerJ)
Plastic pollution is a global threat and occurs in almost every marine ecosystem. The amount of plastic in the ocean has increased substantially over the past decade, posing a mounting threat to biodiversity. Seabirds, typically top predators in marine food chains, have been negatively affected by plastic pollution. Here we explored the sublethal effects of plastic ingested by wedge-tailed shearwaters (Ardenna pacifica) on the island of Maui, Hawai‘ i. Using analyses of blood chemistry, gene expression, morphometrics and regurgitated stomach contents, we investigated the effects of plastic ingestion on adult wedge-tailed shearwaters from three established colonies. We detected plastic in 12 out of 28 birds; however, we did not find significant relationships between ingested plastic, body condition, gene expression and blood analytes. We found a negative relationship between weight, blood urea nitrogen (BUN), hematocrit and potassium, that could reflect body condition in this population. Genes associated with metabolic, biosynthetic pathways, inflammatory responses, and ribosome function were also upregulated in birds placed in a ‘light weight’ category. We suggest that upregulated metabolic activity and elevated levels of hematocrit, BUN and potassium in light weight birds might imply dehydration and a response to increased energetic demand from stressors. Repetitive sampling could better inform whether body condition improves throughout the breeding season. We urge researchers to continue using multiple proxies to study effect of plastic ingestion in free-living populations.